2022
DOI: 10.3390/ijerph19031647
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Performance of Low-Cost Air Quality Monitors in Dallas, Texas

Abstract: The emergence of low-cost air quality sensors may improve our ability to capture variations in urban air pollution and provide actionable information for public health. Despite the increasing popularity of low-cost sensors, there remain some gaps in the understanding of their performance under real-world conditions, as well as compared to regulatory monitors with high accuracy, but also high cost and maintenance requirements. In this paper, we report on the performance and the linear calibration of readings fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…Recent studies comparing low-cost methods on the market to reference methods all suggest that the readings of low-cost sensors are sensitive to environmental factors, such as the relative humidity, and performances against reference monitors change with the weather [42,43,45,46]. Light-absorbing carbon estimates using image-based methods for reflectance may be sensitive to the site, season, pollution source (e.g., fuel type), and/or reference method selected for calibration.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies comparing low-cost methods on the market to reference methods all suggest that the readings of low-cost sensors are sensitive to environmental factors, such as the relative humidity, and performances against reference monitors change with the weather [42,43,45,46]. Light-absorbing carbon estimates using image-based methods for reflectance may be sensitive to the site, season, pollution source (e.g., fuel type), and/or reference method selected for calibration.…”
Section: Discussionmentioning
confidence: 99%
“…Reference CH4 measurements were provided via a research-grade Aeris Ultra gas analyzer (Aeris Ultra, Project Canary, Denver, CO, USA). The inlet of the Aeris gas analyzer was placed adjacent to the XPOD inlet on the roof of the monitoring vehicle to minimize differences in the gas composition during deployment [ 38 ] ( Figure S2 ). The response lags for pumped gas to enter both instruments were equal for the XPOD and Aeris Ultra.…”
Section: Materials and Methodsmentioning
confidence: 99%
“…For measurement of air pollution, several studies revealed that meteorological parameters such as relative humidity (RH), temperature (T), pressure (P), and wind impact the performance of low-cost sensors and therefore there is a need to use standard reference-grade monitoring stations for evaluation and validation. It is further advised to not rely on low-cost air-quality sensors at higher RH value locations [ 125 ].…”
Section: Conclusion and Future Research Directionsmentioning
confidence: 99%
“…To build confidence in low-cost sensors for real-world monitoring, regular calibration and validation with a co-located standard instrument is critical [ 125 ]. Improved statistical methods, IoT-based platforms, and space-based sensors can all improve methodological approaches for environmental pollution.…”
Section: Conclusion and Future Research Directionsmentioning
confidence: 99%